Improving nutrition-sensitive value chains of African indigenous vegetables: current trends in postharvest management and processing - Elolu, Samuel; Byarugaba, Rachel; Opiyo, Arnold Mathew; Nakimbugwe, Dorothy; Mithöfer, Dagmar; Huyskens-Keil, Susanne (Frontiers in Sustainable Food Systems, 2023)
The value chains of African indigenous vegetables (AIVs) are highly constrained by high postharvest losses (up to 50%) along the chain, largely occasioned by poor postharvest management and a lack of optimised processing technologies. The technologies and practices are key technical aspects that can transform the capacity of the chain by enhancing the overall value generated from the system. AIVs have recently experienced an increase in demand due to their high nutritional value and the opportunity they present to enhance rural incomes, since they are predominantly produced by smallholder farmers in rural and peri-urban areas. This implies that they can positively contribute to increased availability and hence supply of nutritious food within local food systems. Furthermore, the fact that half of the economic value of AIVs is potentially lost due to inappropriate postharvest management and inadequate processing demonstrates the potential that related interventions and transformations could have in enhancing and preserving value along AIV value chains. Currently, the approaches applied to reduce food waste, preserve nutritional quality, and add value to AIVs are largely traditional in nature. They require upgrading and need to be aligned towards achieving a nutrition-sensitive value chain. By looking at these as value creation processes, this mini-review examines the current postharvest management practices, highlights relevant new and innovative technologies and related challenges, and suggests potential options to improve the benefits for AIV value chain actors and thus contribute to a sustainable transformation of nutrition-sensitive food systems.